HUBUNGAN KUALITAS INFORMASI IBU TENTANG KESEHATAN REPRODUKSI DENGAN PENGETAHUAN MENSTRUASI PADA SISWI SMPN 10 MATARAM TAHUN 2022 - Fatimah, Siti; Kardi, Kardi (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2023)
Based on data of World Health Organization (WHO) in 2014 the number of Reproductive Tract Infection on teenagers and adult was the highest number in the world. Based on interview on September 20, 2021 toward 10 female students of SMPN 10 Mataram, there were 6 of the female students answered did not know about menstruation, other 8 female students did not get information about menstruation and reproduction health from their mothers. In this regard, it is necessary to carry out study with aimed to know the relationship between mother’s information quality about reproduction health and knowledge about menstruation on female students of SMPN 10 Mataram in 2022. Design of the study was descriptive analysis by cross sectional approach. The population of the study was all female students of SMPN 10 Mataram. Sampling technique by proportional random sampling. Analysis used in this study was univariate and bivariate analyses by Chi Square test with SPSS application. Result of the study showed respondents who got information about health reproduction in good category was 44 respondents (57.9%) who have high knowledge about menstruation; moderate knowledge was 28 (36.8%); low knowledge was 4 (5.3%). Whereas, 3 (50.0%) respondents did not get information but they have moderate knowledge, and other 3 (5-.0%) respondents have low knowledge about menstruation. Based on Chi-Square test with p value= 0.000(p<0.05). Can be concluded that there was a significant relationship between mother’s information quality about reproduction health and knowledge about menstruation on female students of SMPN 10 Mataram in 2022. Suggestion to SMPN 10 Mataram is information about health reproduction from mother is needed by female students to increase knowledge and prepare themselves for menstruation.